Avenanthramide C mitigates cisplatin-induced hippocampal neurotoxicity and cognitive impairment in rats via suppression of neuroinflammation and neuronal apoptosis - Aldubayan, Maha Abdulrahman (Frontiers in Pharmacology, 2025)
IntroductionCisplatin (CP)-induced cognitive impairment, commonly referred to as chemobrain, affects a substantial proportion of patients with cancer and currently lacks an effective pharmacological treatment. This condition is closely linked to neuroinflammation. Avenanthramide C (AVN-C), a bioactive compound uniquely found in oats, is known for its anti-inflammatory, anti-apoptotic, and neuroprotective properties. However, the precise mechanisms underlying its broader protective effects remain incompletely understood. This study aimed to investigate the potential of AVN-C to mitigate or prevent hippocampal damage in rats.MethodsForty male Wistar rats were randomly divided into four groups (n = 10 per group): Control (5%DMSO/Saline), CP (8 mg/kg), AVN-C (6 mg/kg), and CP + AVN-C. AVN-C was administered orally once daily, while CP was delivered intraperitoneally on days 1, 4, and 7. Body weight and survival were monitored daily. Cognitive performance was assessed through behavioral tests, followed by biochemical analyses of hippocampal tissue. Inflammatory markers, NF-κB, TNF-α, IL-6, and IL-1β, and apoptotic markers (caspase-3 and BAX) were quantified.ResultsCP administration resulted in significant reductions in body weight and survival. In contrast, co-treatment with AVN-C ameliorated these effects, markedly reducing hippocampal levels of NF-κB, TNF-α, IL-6, IL-1β, caspase-3, and BAX. Histopathologically, hippocampal tissues treated with CP + AVN-C were less damaged than tissues treated with the CP group. In conclusion, AVN-C significantly improved spatial learning and working memory in CP-treated rats and attenuated neuroinflammatory and apoptotic signaling.DiscussionThese findings support the potential of AVN-C as a therapeutic agent for mitigating CP-induced neurotoxicity and cognitive dysfunction.